Potensi Media Sosial Dalam Pembelajaran Biologi: Analisis Kemampuan Digital Generasi Z - Sherly Mega Andriyani; Anisa Oktina Sari Pratama; Irwandani Irwandani (Lembaga Bale Literasi, 2026)
This study investigates the potential of social media in biology learning by examining the digital competence of Generation Z through a Systematic Literature Review (SLR). The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework to ensure methodological rigor and transparency. A total of 18 relevant documents published in Indonesia between 2015 and May 2025 were identified and analyzed. The inclusion criteria focused on studies addressing social media, biology learning, digital competence, and Generation Z. The findings reveal that platforms such as YouTube, Instagram, TikTok, and WhatsApp are widely utilized in learning activities, supporting concept visualization, collaboration, and creative engagement. Most of the reviewed studies were conducted at secondary and higher education levels, reflecting the broad adoption of social media in formal education. Generation Z demonstrates strong digital competence in communication, collaboration, and content creation. However, challenges remain in critical information evaluation, ethical digital practices, and the pedagogical integration of social media. This review highlights the dual role of social media as both an opportunity and a challenge in digital-era education. Strengthening Generation Z’s digital competence is essential to fully harness the educational potential of social media while addressing issues of information credibility and responsible use. This study contributes to mapping research trends on digital competence and provides insights for educators and policymakers seeking to optimize social media use in 21st-century learning.